Blood Lactate Response, Oxygen Consumption, and Muscle Activity during Treadmill Running with Constraint. Issue 1 (August 2014) - Haudum, A.; Birklbauery, J.; Sieghartsleitner, R.; Gonaus, C.; Müller, E.
The induction of self-organization during running with a special harness may lead to reduced energy requirements. This experiment was designed to investigate the effect of practicing with a rubber tubing constraint attached between the heel and the hip for 7 wk. (18 treadmill running sessions) on oxygen consumption, caloric unit cost, blood lactate concentration, and muscle activity. 18 male recreational runners ( M age = 26.3yr.) were assigned to either an intervention or a control group. The intervention group trained with the constraint and the control group trained without it. Test 1 was conducted before the intervention, Test 2 after the intervention, and Test 3 7 wk. after Test 2 (no training between Tests 2 and 3). At Test 1, lactate and muscle activity were significantly increased during constrained running. For lactate, a significant decrease was found in the intervention group for running with the constraint; at Test 3, lactate returned to Test 1 level. No notable changes occurred in the physiological parameters. Furthermore, there was no observed transfer effect on normal running.